A microgel assembly material and its preparation method and application

Through the synergistic effect of the phenylboric acid-modified polymer solution and the microgel, an injectable and self-healing microgel assembly material is formed, which solves the problem of uncontrollable microgel distribution and improves cell survival and therapeutic effect.

CN115068695BActive Publication Date: 2024-12-13ASIA REGENERATIVE MEDICINE LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210608514.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2024-12-13
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

Microgels are difficult to fix at the injection site after being injected into the human body, resulting in uncontrollable distribution and affecting cell survival and therapeutic effect.

Method used

The phenylboric acid modified polymer solution and microgel are synergistically used to achieve rapid self-assembly of microgels, forming microgel assembly materials with porous, injectable and self-healing properties. , ensure that the distribution at the injection site is controllable.

Benefits of technology

It realizes rapid self-assembly and self-healing of microgels, reduces the difficulty and time of surgery, improves cell viability and vascularization process, and is suitable for a variety of minimally invasive treatment needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115068695B_ABST
    Figure CN115068695B_ABST
Patent Text Reader

Abstract

The present invention discloses a microgel assembly material and a preparation method and application thereof. The raw materials for preparing the assembly material include microgels and a phenylboronic acid-modified polymer solution, and the phenylboronic acid-modified polymer solution penetrates between the microgels through the action of capillary force and forms a dynamic chemical bond with the microgels. The microgel assembly material in the present invention utilizes the synergistic effect of capillary penetration and dynamic chemical bonds to achieve rapid self-assembly of microgels, and has the characteristics of microporosity, injectability, self-healing, biocompatibility, and controllable distribution at the injection site, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a microgel assembly material and a preparation method and application thereof. Background Art

[0002] Cell therapy has the advantages of good efficacy, wide treatment range, and low toxic side effects, and has become a hot topic of medical research in recent years. Although cell therapy has been used clinically to achieve certain therapeutic effects, some defects have emerged during the treatment process: such as severe cell loss and low cell survival rate after transplantation. Microgels have high water content, similar components to the extracellular matrix, and good biocompatibility. They can wrap cells in hydrogel materials, which not only provide cells with a three-dimensional support, but also prevent cells from being damaged by shear forces during injection and transplantation. Although microgels can achieve injectable minimally invasive treatment, they are difficult to fix at the injection site after being injected into the human body, resulting in uncontrollable distribution. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a microgel assembly material which has the characteristics of being injectable, self-healing and controllable distribution at the injection site.

[0004] The invention also provides a method for preparing the microgel assembly material.

[0005] The present invention also provides a 3D cell culture carrier.

[0006] The present invention also provides a biomaterial.

[0007] The invention also provides a medical product.

[0008] The present invention also proposes the application of the microgel assembly material.

[0009] In a first aspect of the present invention, a microgel assembly material is proposed. The raw materials for preparing the assembly material include microgels and a phenylboronic acid-modified polymer solution. The phenylboronic acid-modified polymer solution penetrates between the microgels through capillary force and forms dynamic chemical bonds with the microgels.

[0010] The microgel assembly material according to the embodiment of the present invention has at least the following beneficial effects:

[0011] The microgel assembly material of the present invention utilizes the synergistic effect of capillary permeation and dynamic chemical bonds to achieve rapid self-assembly of microgels, and has microporosity, injectability, self-healing and biocompatibility. At the same time, the distribution of the microgel assembly material at the injection site is controllable and easy to track. Specifically:

[0012] The microgel assembly material is a microgel assembly network, and its preparation method is simple and easy, and is applicable to a variety of microgel monomers (including microgels made from different raw materials), so that the assembly of microgels can be achieved under mild conditions; the microgel assembly material can be stably assembled under physiological conditions, has injectability and self-healing ability, can meet the needs of minimally invasive treatment, will not be lost with body fluids, and has controllable distribution at the injection site, reducing the difficulty and time of surgery, and can still restore to its original shape after being damaged by external forces; the microgel assembly material can be used to wrap different cells, creating a heterogeneous cell microenvironment at the microscale, which can induce cell reorganization and vascularization. The microgel assembly material is porous, and the interconnected micropores and void spaces inside it not only accelerate the mass transfer of nutrients, thereby improving the viability of cells, but also facilitate cell penetration and vascularization without waiting for the degradation of hydrogels.

[0013] Therefore, the microgel assembly material of the present invention has good application prospects in the fields of biomedical materials, tissue engineering and regenerative medicine.

[0014] The phenylboric acid modified polymer solution comprises a phenylboric acid modified polymer material.

[0015] In some embodiments of the present invention, the mass ratio of the microgel to the phenylboric acid modified polymer material in the phenylboric acid modified polymer solution is (6-2000):1.

[0016] Microgel assembly materials are based on the coordination of dynamic chemical bonds and capillary forces. By adjusting the ratio of microgels and phenylboronic acid-modified polymers, a variety of microgel ball stacking forms (such as dense stacking and loose stacking) can be obtained to meet the needs of different minimally invasive injection treatments. Specifically, different stacking forms are suitable for transplantation in different parts of the body. For example, the greater omentum in the abdomen is a layer of membrane with a rich vascular network between organs. Transplantation of grafts in the greater omentum in the abdomen needs to adapt to the complex environment between organs, so a loose stacking form is required, that is, the gaps between the microgel balls are larger, and the degradation of the connecting materials used for assembly is more conducive to the growth of blood vessels. In the application field of cartilage repair, microgel assemblies require denser stacking to ensure that the assembly materials have a certain shape and better mechanical strength.

[0017] The microgel assembly material of the present invention is porous, and the interconnected micropores and void spaces inside it not only accelerate the mass transfer of nutrients, thereby improving the viability of cells, but also facilitate cell penetration and vascularization without waiting for the degradation of the hydrogel.

[0018] In some preferred embodiments of the present invention, the mass ratio of the microgel to the phenylboric acid-modified polymer material in the phenylboric acid-modified polymer solution is (25-1000):1.

[0019] In some embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer solution is (0.5-20):1.

[0020] In some embodiments of the present invention, the mass fraction of the phenylboric acid modified polymer material in the phenylboric acid modified polymer solution is 1-8%.

[0021] In some preferred embodiments of the present invention, the phenylboric acid modified polymer solution is an aqueous solution of a phenylboric acid modified polymer material.

[0022] In some embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer material is less than or equal to 50:1, and the microgels in the microgel assembly material are loosely stacked.

[0023] In some embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer material is greater than 50:1 and less than or equal to 1000:1, and the microgels in the microgel assembly material are densely packed.

[0024] In some preferred embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer material is (100-800):1, and the microgels in the microgel assembly material are densely packed.

[0025] In some more preferred embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer material is (100-400):1, and the microgels in the microgel assembly material are densely packed.

[0026] In some embodiments of the present invention, the mass ratio of the microgel to the phenylboronic acid modified polymer material is greater than 1000:1, and the microgels in the microgel assembly material are loosely stacked.

[0027] Compared with the mass ratio of microgel to phenylboronic acid modified polymer material being less than 1000:1, the mass ratio of microgel to phenylboronic acid modified polymer material being too large (greater than 1000:1), the assembly effect is poor, such as partial assembly, because the dynamic chemical bonds that can be provided to the phenylboronic acid modified polymer are limited.

[0028] In some embodiments of the present invention, the mass fraction of the phenylboric acid modified polymer material in the phenylboric acid modified polymer solution is 2%, the mass ratio of the microgel to the phenylboric acid modified polymer solution is (2-8):1, and the microgels in the microgel assembly material are densely packed.

[0029] In some preferred embodiments of the present invention, the close packing includes hexagonal close packing.

[0030] In some preferred embodiments of the present invention, the close packing includes surface packing or volume packing.

[0031] The surface stacking means that the number of stacking layers of the microgel balls in only one dimension does not exceed 3, and the volume stacking means that the number of stacking layers of the microgel balls in three dimensions exceeds 3.

[0032] In some embodiments of the present invention, the raw materials for preparing the phenylboric acid-modified polymer material in the phenylboric acid-modified polymer solution include phenylboric acid compounds and polymer materials.

[0033] In some preferred embodiments of the present invention, the polymer material and a phenylboronic acid compound are subjected to an amidation reaction to obtain the phenylboronic acid-modified polymer material.

[0034] In some preferred embodiments of the present invention, the polymer material is a polymer material containing a carboxyl group, and the phenylboric acid is aminophenylboric acid; or, the polymer material is a polymer material containing an amino group, and the phenylboric acid is carboxylphenylboric acid.

[0035] In some more preferred embodiments of the present invention, the carboxyl-containing polymer material includes at least one of sodium carboxymethyl cellulose, chondroitin sulfate, hyaluronic acid, gelatin, carboxymethyl chitosan, collagen or sodium alginate; the amino-containing polymer material includes at least one of carboxymethyl chitosan, polylysine or polyethylene imine.

[0036] In some more preferred embodiments of the present invention, the carboxyl groups in the carboxyl-containing polymer material are activated and then undergo an amidation reaction with the amino groups in aminophenylboronic acid to obtain the phenylboronic acid-modified polymer material.

[0037] In some preferred embodiments of the present invention, the mass ratio of the phenylboric acid compound to the polymer material is (1-10):1.

[0038] In some embodiments of the present invention, the phenylboric acid-modified polymer material includes phenylboric acid-modified sodium carboxymethyl cellulose.

[0039] Sodium carboxymethyl cellulose modified with phenylboronic acid, referred to as CMC-BA.

[0040] In some embodiments of the present invention, the phenylboronic acid-modified polymer material includes a phenylboronic acid-modified natural polymer material.

[0041] In some embodiments of the invention, the dynamic chemical bond comprises a borate ester bond.

[0042] In some embodiments of the present invention, the assembly material is a microgel assembly material containing alcoholic hydroxyl groups.

[0043] In some preferred embodiments of the present invention, the microgel comprises alcoholic hydroxyl groups.

[0044] In some more preferred embodiments of the present invention, the pore size of the microgel is 20-60 nm.

[0045] In some more preferred embodiments of the present invention, the porosity of the microgel is 60%-80%.

[0046] In some embodiments of the present invention, the raw material for preparing the microgel includes polyvinyl alcohol.

[0047] Polyvinyl alcohol, referred to as PVA.

[0048] In some preferred embodiments of the present invention, the raw materials for preparing the microgel further include water-soluble photosensitive polymerizable monomers.

[0049] In some more preferred embodiments of the present invention, the mass ratio of the polyvinyl alcohol to the water-soluble photosensitive polymerizable monomer is (0.8-1.2):1.

[0050] In some more preferred embodiments of the present invention, the water-soluble photosensitive polymerizable monomer includes at least one of polyethylene glycol diacrylate, methacrylated gelatin, methacrylated sodium alginate, methacrylated hyaluronic acid, methacrylated silk fibroin or methacrylated chitosan.

[0051] Polyethylene glycol diacrylate, referred to as PEGDA; methacryloyl gelatin, referred to as GelMA; methacryloyl sodium alginate, referred to as AlgMA; methacryloyl hyaluronic acid, referred to as HAMA; methacryloyl silk fibroin, referred to as SilMA; methacryloyl chitosan, referred to as CSMA.

[0052] In some preferred embodiments of the present invention, the microgel is a semi-interpenetrating network microgel.

[0053] In some more preferred embodiments of the present invention, the semi-interpenetrating network is a cross-linked polymer network obtained by polymerization of a linear polyvinyl alcohol network and a water-soluble photosensitive monomer.

[0054] In some embodiments of the present invention, the microgel is a microgel encapsulating cells, cell groups or cell tissues.

[0055] In some preferred embodiments of the present invention, the cells include at least one of fibroblasts, kidney cells, pancreatic islet cells or hepatocytes.

[0056] The second aspect of the present invention provides a method for preparing a microgel assembly material, comprising the following steps: allowing a phenylboronic acid-modified polymer solution to penetrate between microgels through capillary force and construct dynamic chemical bonds with the microgels to obtain the assembly material.

[0057] The method for preparing a microgel assembly material according to an embodiment of the present invention has at least the following beneficial effects: the preparation method is a method for preparing a microgel capable of rapid self-assembly and self-healing based on capillary permeation and dynamic chemical bonds, and the preparation method provides a general strategy for microgel assembly, which is simple and easy to implement and applicable to a variety of microgel monomers (including microgels made from different raw materials), so that the assembly of microgels can be achieved under mild conditions.

[0058] In some embodiments of the present invention, the phenylboric acid modified polymer solution is an aqueous solution of a phenylboric acid modified polymer material.

[0059] In some embodiments of the present invention, the method for preparing the microgel assembly material includes the following steps: the raw materials for preparing the microgel include polyvinyl alcohol and a water-soluble photosensitive polymerization monomer, an aqueous solution of the phenylboronic acid-modified polymer material is added dropwise to the microgel, the phenylboronic acid-modified polymer solution penetrates between the microgels through capillary force, and constructs dynamic chemical bonds with the microgels to obtain the assembly material.

[0060] The preparation method of the microgel assembly material in the present invention is a universal microgel assembly method, that is, it can be achieved by introducing PVA into any hydrogel polymerized by light-initiated water-soluble photosensitive polymerization monomers, without further modification and modification of the polymer. Specifically, the present invention uses the capillary force of the internal gaps of the microgel to make the phenylboronic acid modified polymer material penetrate and fill the inside of the microgel, and obtains a microgel assembly network based on the dynamic bonding action constructed by the phenylboronic acid group and polyvinyl alcohol, that is, the microgel assembly material.

[0061] In some embodiments of the present invention, the method for preparing the microgel assembly material includes the step of preparing a phenylboronic acid-modified polymer material, specifically comprising: an amino-containing polymer material undergoes an amidation reaction with carboxyl phenylboronic acid to obtain the phenylboronic acid-modified polymer material.

[0062] In some embodiments of the present invention, the method for preparing the microgel assembly material includes the step of preparing a phenylboronic acid-modified polymer material, specifically comprising: after the carboxyl group-containing polymer material is activated, an amidation reaction occurs with aminophenylboronic acid to obtain the phenylboronic acid-modified polymer material.

[0063] In some preferred embodiments of the present invention, the step of preparing the phenylboronic acid modified polymer material comprises the following steps:

[0064] S1-1, dissolving the polymer material in PBS buffer, adding a carboxyl activator and aminophenylboronic acid, reacting to obtain a crude product;

[0065] S1-2, the crude product is dialyzed with deionized water and freeze-dried to obtain a phenylboronic acid modified polymer material.

[0066] In some more preferred embodiments of the present invention, the carboxyl activating agent is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide.

[0067] 1-(3-Dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, referred to as EDC; N-hydroxysuccinimide, referred to as NHS.

[0068] In some more preferred embodiments of the present invention, the activation time of the carboxyl group is 0.5-3h.

[0069] In some more preferred embodiments of the present invention, in step S1-1, the reaction step is carried out at room temperature for 24-72 hours.

[0070] In some more preferred embodiments of the present invention, in step S1-1, the ratio of the amount of the polymer material to the amount of the PBS buffer is (0.9-1.1) g:100 mL.

[0071] In some more preferred embodiments of the present invention, in step S1-1, the mass ratio of the polymer material, the EDC and the NHS is (1.9-2.1): (1.92-1.95): (1.14-1.18).

[0072] In some more preferred embodiments of the present invention, in step S1-2, the crude product is dialyzed against deionized water for 3 days.

[0073] In some embodiments of the present invention, the method for preparing the microgel assembly material further includes a step of preparing the microgel, specifically comprising: using polyvinyl alcohol and a water-soluble photosensitive polymerization monomer as polymerization monomers and adopting microfluidic technology to prepare the microgel.

[0074] In some preferred embodiments of the present invention, the method for preparing the microgel comprises the following steps:

[0075] S2-1, mixing a mixed solution of polyvinyl alcohol and a water-soluble photosensitive polymerizable monomer with a photoinitiator to obtain a mixture;

[0076] S2-2, using the mixture as the aqueous phase, and preparing the microgel through microfluidics technology and photo-initiated polymerization.

[0077] In some more preferred embodiments of the present invention, in step S2-1, the mixed solution of polyvinyl alcohol and a water-soluble photosensitive polymerizable monomer is a mixed aqueous solution of polyvinyl alcohol and a water-soluble photosensitive polymerizable monomer.

[0078] In some more preferred embodiments of the present invention, in step S2-1, the mass fraction of the water-soluble photosensitive polymerizable monomer in the mixture is 1-20%.

[0079] In some more preferred embodiments of the present invention, in step S2-1, the mass fraction of the water-soluble photosensitive polymerizable monomer in the mixture is 5-20%.

[0080] In some more preferred embodiments of the present invention, in step S2-1, polyvinyl alcohol, water-soluble photosensitive polymerizable monomers and PBS buffer are mixed to obtain the mixed solution.

[0081] In some more preferred embodiments of the present invention, in step S2-1, in the mixed solution, the ratio of the amount of polyvinyl alcohol, the water-soluble photosensitive polymerizable monomer and the PBS buffer is (0.8-1.2) g: 1 g: (18-22) mL.

[0082] In some more preferred embodiments of the present invention, in step S2-1, the photoinitiator includes phenyl (2,4,6-trimethylbenzoyl) phosphate lithium salt.

[0083] Lithium phenyl (2,4,6-trimethylbenzoyl) phosphate, referred to as LAP.

[0084] In some more preferred embodiments of the present invention, in step S2-1, the mixed solution is mixed with a photoinitiator to obtain a mixture.

[0085] In some more preferred embodiments of the present invention, in the mixture, the mass fraction of the photoinitiator is 0.1-3%.

[0086] In some more preferred embodiments of the present invention, in step S2-1, the mass ratio of polyvinyl alcohol, water-soluble photosensitive polymerizable monomer and photoinitiator is (0.8-1.2):1:(0.03-0.05).

[0087] In some more preferred embodiments of the present invention, in step S2-1, a mixed solution of polyvinyl alcohol and a water-soluble photosensitive polymerizable monomer is mixed with a photoinitiator, filtered and sterilized, and then mixed with a biological cell resuspension to obtain a mixture.

[0088] In some more preferred embodiments of the present invention, in step S2-2, the mixture is used as the aqueous phase, and the aqueous phase and the oil phase are mixed using microfluidic technology to prepare W / O microdroplets, which are then irradiated to obtain the microgel.

[0089] In some more preferred embodiments of the present invention, in step S2-2, the flow rate ratio of the oil phase to the water phase is (10-40):1.

[0090] In some more preferred embodiments of the present invention, in step S2-2, the wavelength of the light is 405-420 nm.

[0091] In some more preferred embodiments of the present invention, in step S2-2, the illumination time is 1-5 min.

[0092] In some more preferred embodiments of the present invention, in step S2-2, the oil phase is fluorinated oil HFE-7500 containing a non-ionic fluorocarbon surfactant.

[0093] In some more preferred embodiments of the present invention, in step S2-2, in the preparation of the oil phase, the volume ratio of the nonionic fluorocarbon surfactant to the fluorinated oil HFE-7500 is (1-4): 9. In some more preferred embodiments of the present invention, in step S2-2, after the W / O microdroplets are cross-linked to form microgel spheres, they are washed with fluorinated oil HFE7500, then washed 3 times with PBS solution, and then transferred to PBS solution for storage.

[0094] The third aspect of the present invention provides a 3D cell culture carrier, comprising the above-mentioned microgel assembly material.

[0095] The fourth aspect of the present invention provides a biomaterial comprising the above-mentioned microgel assembly material.

[0096] In some embodiments of the invention, the biomaterial comprises an implant material.

[0097] The fifth aspect of the present invention provides a medical product comprising the above-mentioned microgel assembly material.

[0098] In some embodiments of the present invention, the medical product includes a medical material or a medical device.

[0099] The sixth aspect of the present invention proposes the use of the above-mentioned microgel assembly material in the preparation of biomaterials or medical products. BRIEF DESCRIPTION OF THE DRAWINGS

[0100] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0101] Figure 1This is a photo of the hydroxyl-containing microgel assembly material in Example 1-2 of the present invention;

[0102] Figure 2 This is a photo of the hydroxyl-containing microgel assembly material in Example 3-4 of the present invention;

[0103] Figure 3 This is a diagram showing the experimental results of splicing slices of the hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0104] Figure 4 This is a diagram showing the results of a tensile test of a slice of a hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0105] Figure 5 This is a diagram showing the injectability test results of the hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0106] Figure 6 This is a graph showing the mechanical properties test results of the hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0107] Figure 7 This is a microscopic morphology test result diagram of the surface of the hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0108] Figure 8 This is a microscopic morphology test result diagram of the cross section of the hydroxyl-containing microgel assembly material in Example 4 of the present invention;

[0109] Fig. 9 This is a graph showing the cell survival status test results of the hydroxyl-containing microgel assembly material in Example 5 of the present invention;

[0110] Fig.10 This is a photo of the hydroxyl-containing microgel assembly material in Example 6 of the present invention;

[0111] Fig.11 This is a photo of the hydroxyl-containing microgel assembly material in Comparative Example 1 of the present invention;

[0112] Fig.12 This is a photo of the hydroxyl-containing microgel assembly material in Comparative Example 2 of the present invention;

[0113] Fig.13 This is a photograph of the hydroxyl-containing microgel assembly material in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0114] The following will clearly and completely describe the concept of the present invention and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work all belong to the scope of protection of the present invention. In the description of the present invention, the meaning of several is more than one, the meaning of more than two is more than, greater than, less than, exceed, etc. are understood to exclude the number itself, and above, below, within, etc. are understood to include the number itself.

[0115] Drug information used in the examples and comparative examples:

[0116] The pH value of PBS solution (also called phosphate buffer solution) is about 7.4;

[0117] Sodium carboxymethyl cellulose: viscosity: 600-3000mPa.s, McLean, C804625;

[0118] PEGDA: polyethylene glycol diacrylate, average molecular weight ∼700, MacLean;

[0119] PVA: polyvinyl alcohol 1799, alcoholysis degree: 98-99% (mol / mol), MacLean;

[0120] Nonionic fluorocarbon surfactant: 10% W / V, Shenzhen Huanuo Biotechnology Co., Ltd., HN-surf-1g;

[0121] Carboxymethyl chitosan: degree of substitution 85%, Adamas, 105764B.

[0122] Aminophenylboronic acid: 3-aminophenylboronic acid, Adamas, 46456E;

[0123] Carboxyphenylboronic acid: 4-carboxyphenylboronic acid, Adamas, 22954B;

[0124] The cells (cell populations) used in the examples are all commercially available (or obtained by self-differentiation).

[0125] Example 1

[0126] This embodiment discloses a hydroxyl-containing microgel assembly material, the preparation process of which includes:

[0127] (I) Preparation of phenylboronic acid modified natural polymer materials:

[0128] Dissolve 2g of sodium carboxymethylcellulose (CMC) in 200mL of PBS buffer. Add EDC (1.936g) and NHS (1.164g) to the above solution, stir for 30 minutes, then add 2g of aminophenylboronic acid, and react at room temperature for 24h (the reaction time can be 24-72h). The crude product is dialyzed with deionized water for 3 days, then freeze-dried to obtain phenylboronic acid-modified sodium carboxymethylcellulose (CMC-BA).

[0129] (II) Preparation of semi-IPN microgels:

[0130] Take 5g PVA and 5g PEGDA and dissolve them in 100mL PBS solution, then add 0.2g phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) and stir until completely dissolved to obtain PEGDA-PVA precursor solution as the water phase. Take 1mL non-ionic carbon fluorosurfactant (10% W / V), add 9mL fluorinated oil HFE-7500 to obtain non-ionic carbon fluorosurfactant solution (1% W / V), and stir evenly to obtain the oil phase. The solutions of the water phase and the oil phase are prepared into W / O microdroplets using microfluidic technology, wherein the flow rates of the water phase and the oil phase are set to 0.3mL / h and 2.7mL / h, respectively. Collect the microdroplets generated in the microfluidic chip and place them under blue light (405-420nm) for 2min to crosslink the PEGDA-PVA microdroplets into microgel spheres. After washing with fluorinated oil HFE7500 and washing with PBS solution for 3 times, the spheres were transferred to PBS solution for storage to obtain PEGDA-PVA microgel spheres.

[0131] (III) Using water as solvent, a 2% CMC-BA aqueous solution was prepared. 1 g of PEGDA-PVA microgel spheres were placed in a round petri dish, and 0.5 g of CMC-BA aqueous solution was dripped onto the accumulated microgel spheres. The capillary force of the internal voids of the microgel spheres caused them to penetrate, fill, and react to the inside, forming a microgel assembly network, thereby obtaining a microgel assembly material.

[0132] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0133] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0134] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0135] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0136] Example 2

[0137] This embodiment discloses a hydroxyl-containing microgel assembly material, which is different from Example 1 in that: in step (III) of its preparation process: the amount of the PEGDA-PVA microgel spheres used is 0.5 g.

[0138] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0139] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0140] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0141] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0142] Example 3

[0143] This embodiment discloses a hydroxyl-containing microgel assembly material, which is different from Example 1 in that: in step (III) of its preparation process: the amount of the PEGDA-PVA microgel spheres used is 2 g.

[0144] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0145] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0146] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0147] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0148] Example 4

[0149] This embodiment discloses a hydroxyl-containing microgel assembly material, which is different from Example 1 in that: in step (III) of its preparation process: the amount of the PEGDA-PVA microgel spheres used is 4 g.

[0150] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0151] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0152] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0153] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0154] Example 5

[0155] This embodiment discloses a hydroxyl-containing microgel assembly material, the preparation process of which includes:

[0156] (I) Preparation of phenylboronic acid modified natural polymer material: Dissolve 2 g of sodium carboxymethyl cellulose (CMC) in 200 mL of PBS buffer. Add EDC (1.936 g) and NHS (1.164 g) to the above solution, stir for 30 minutes, and then add 2 g of aminophenylboronic acid. The crude product is dialyzed with deionized water for 3 days and then freeze-dried to obtain phenylboronic acid modified sodium carboxymethyl cellulose (CMC-BA). 60 Co ray sterilization, for future use. Other reagents and equipment used in the experiment were sterilized by high temperature, high pressure and filtration, and the entire experimental process was completed in a sterile environment.

[0157] (II) Preparation of semi-IPN microgels: 5 g of PVA and 5 g of PEGDA were dissolved in 100 mL of PBS solution, and then 0.2 g of phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) was added and stirred until completely dissolved to obtain a PEGDA-PVA precursor solution. After filtration and sterilization, a pancreatic islet cell suspension mixed with DMEM medium was added to the PEGDA-PVA precursor solution as an aqueous phase (the volume percentage concentration of the cell suspension was 10%, and the biological cell count in the cell resuspension was about 1×10 6 / mL, the culture medium is complete DMEM culture medium containing 10% fetal bovine serum and 1% double antibody). Take 1mL of non-ionic carbon fluorosurfactant (10% W / V), add 9mL of fluorinated oil HFE-7500 to obtain a non-ionic carbon fluorosurfactant solution (1% W / V), stir evenly, filter and sterilize to obtain the oil phase. The aqueous and oil phase solutions are prepared into W / O microdroplets using microfluidic technology, wherein the flow rates of the aqueous and oil phases are set to 0.3mL / h and 2.7mL / h, respectively. The microdroplets generated in the microfluidic chip are collected and irradiated under blue light (405-420nm) for 2min to crosslink the PEGDA-PVA microdroplets into microgel balls. After washing with fluorinated oil HFE7500, wash 3 times with PBS solution, and then transfer to PBS solution for storage to obtain PEGDA-PVA microgel balls.

[0158] (III) Using water as solvent, a 2% CMC-BA aqueous solution was prepared. 1 g of PEGDA-PVA microgel spheres were placed in a round petri dish, and 0.5 g of CMC-BA aqueous solution was dripped onto the accumulated microgel spheres. The capillary force of the internal voids of the microgel spheres caused them to penetrate, fill, and react to the inside, forming a microgel assembly network, thereby obtaining a microgel assembly material.

[0159] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0160] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0161] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0162] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0163] Example 6

[0164] (I) Preparation of phenylboronic acid modified polymer materials:

[0165] Dissolve 2g of carboxymethyl chitosan (CS) in 200mL of PBS buffer. Add EDC (1.936g) and NHS (1.164g) to the above solution, stir for 30 minutes, then add 2g of carboxyphenylboronic acid, and react at room temperature for 24h (the reaction time can be 24-72h). The crude product is dialyzed with deionized water for 3 days and then freeze-dried to obtain carboxymethyl chitosan (CS-BA) modified with phenylboronic acid.

[0166] (II) Preparation of semi-IPN microgels:

[0167] Take 5g PVA and 5g PEGDA and dissolve them in 100mL PBS solution, then add 0.2g phenyl (2,4,6-trimethylbenzoyl) lithium phosphate (LAP) and stir until completely dissolved to obtain PEGDA-PVA precursor solution as the water phase. Take 1mL non-ionic carbon fluorosurfactant (10% W / V), add 9mL fluorinated oil HFE-7500 to obtain non-ionic carbon fluorosurfactant solution (1% W / V), and stir evenly to obtain the oil phase. The solutions of the water phase and the oil phase are prepared into W / O microdroplets using microfluidic technology, wherein the flow rates of the water phase and the oil phase are set to 0.3mL / h and 2.7mL / h, respectively. Collect the microdroplets generated in the microfluidic chip and place them under blue light (405-420nm) for 2min to crosslink the PEGDA-PVA microdroplets into microgel spheres. After washing with fluorinated oil HFE7500 and washing with PBS solution for 3 times, the spheres were transferred to PBS solution for storage to obtain PEGDA-PVA microgel spheres.

[0168] (III) A 2% CS-BA aqueous solution was prepared with water as solvent. 2 g of PEGDA-PVA microgel spheres were placed in a round petri dish, and 0.5 g of CS-BA aqueous solution was dripped onto the accumulated microgel spheres. The capillary force of the internal voids of the microgel spheres caused the microgel spheres to penetrate, fill, and react to form a microgel assembly network, thereby obtaining a microgel assembly material.

[0169] This embodiment also provides a 3D cell culture carrier, including the microgel assembly material prepared by the above operation.

[0170] This embodiment also provides a biomaterial, including the microgel assembly material prepared by the above operation.

[0171] This embodiment also provides a medical material, including the microgel assembly material prepared by the above operation.

[0172] This embodiment also provides a medical device, including the microgel assembly material prepared by the above operation.

[0173] The pore size of the microgels prepared in Examples 1-6 is 20-60 nm, and the porosity is 60%-80%.

[0174] Comparative Example 1

[0175] This comparative example discloses a microgel assembly material, which is different from Example 1 in that unmodified CMC is used to replace the CMC-BA in Example 1, that is, in this comparative example, a CMC aqueous solution is dripped onto the stacked PEGDA-PVA microgel balls to prepare the microgel assembly material, wherein the mass fraction of CMC in the CMC aqueous solution is 2%.

[0176] Comparative Example 2

[0177] This comparative example discloses a microgel assembly material, which is different from Example 1 in that: in step (II) of its preparation process: PVA is not added to the aqueous phase, and the prepared microgel is a PEGDA microgel without PVA.

[0178] Comparative Example 3

[0179] This comparative example discloses a microgel assembly material, which is different from Example 1 in that:

[0180] In step (II): CMC-BA is added to the aqueous phase (the mass fraction of CMC-BA in the aqueous phase is 2%), and PVA is not added to the aqueous phase. The microgel prepared in this embodiment is PEGDA-CMC-BA microgel;

[0181] In step (III), a PVA aqueous solution with a mass fraction of 10% is used to replace the CMC-BA aqueous solution in Example 1.

[0182] Test example

[0183] This test example tests the microgel assembly material obtained in the embodiment, specifically:

[0184] (1) The microgel assembly material prepared in Example 1-2 is shown in the following photo Figure 1 As shown: Figure 1 The left picture in the middle is the microgel assembly material prepared in Example 1, and the right picture is the microgel assembly material prepared in Example 2. Figure 1 It can be seen that by changing the ratio of CMC-BA and microgel, microgel assembly materials with different stacking forms of microgel balls can be obtained. When the proportion of microgel is large (the mass ratio of microgel to CMC-BA is above 100:1), the microgel presents a densely packed form, while when the proportion of CMC-BA is large (the mass ratio of microgel to CMC-BA is below 50:1), the microgel is loosely assembled. Figure 1 In the right picture, it can be observed that there are gaps directly between the microgel spheres.

[0185] (2) The microgel assembly material prepared in Example 3-4 is shown in the following photo Figure 2 As shown: Figure 2 The left picture in the middle is the microgel assembly material prepared in Example 3, and the right picture is the microgel assembly material prepared in Example 4. Figure 2 It can be seen that the microgel assembly network of different dense packing forms of microgel spheres can be obtained by utilizing capillary penetration and dynamic bond interaction, including surface stacking or volume stacking.

[0186] (3) The microgel assembly material prepared in Example 4 (the stacking form of the microgel spheres includes hexagonal close packing) was subjected to a macroscopic self-healing experiment to further explore its self-healing ability. Specifically, the prepared microgel assembly material was cut into two pieces, each slice was stained with rhodamine B and methylene blue, respectively, and then the stained slices were spliced ​​together. Without any external intervention, after being placed at room temperature for 10 minutes, it was found that the splicing interface of the sample (stained slice) became blurred and could be pulled with tweezers (such as Figure 3 ), and the spliced ​​microgel assembly material slices will not separate under stretching and can be stretched to twice their original length (as shown Figure 4 ), showing excellent self-healing performance.

[0187] (4) The injectability test results of the microgel assembly material prepared in Example 4 are as follows: Figure 5 As shown, the microgel assembly material can be extruded through a 21G syringe because the microgels therein have a small size, and after extrusion, the microgels in the microgel assembly material still maintain a spherical shape without breaking.

[0188] (5) The mechanical properties of the microgel assembly material prepared in Example 4 were characterized using a universal testing machine. The tensile properties of the sample were tested according to GB / T1040.2-2006 at a tensile speed of 10 mm / min. The test results are as follows: Figure 6 As shown. Figure 6 It can be seen that the microgel self-assembled material has a certain tensile strength and can withstand an external force of 18kPa when the strain is 20%.

[0189] (6) The surface micromorphology of the microgel assembly material prepared in Example 4 is characterized as follows: Figure 7 As shown in FIG, the specific testing method is to freeze-dry the microgel assembly material, then perform gold spraying, and observe the surface microstructure using a field emission scanning electron microscope. Figure 7 It can be seen that the microgel spheres are tightly stacked together, indicating that the microgels are successfully assembled into a whole by utilizing the coordinated effect of capillary forces and dynamic chemical bonds (including borate bonds).

[0190] (7) The microscopic morphology of the cross-section of the microgel assembly material prepared in Example 4 is as follows: Figure 8 As shown in the figure, the specific test conditions are to fracture the microgel assembly material under liquid nitrogen, then perform gold spraying, and observe the microscopic morphology of the cross section using a field emission scanning electron microscope. Figure 8It can be seen that there are many wrinkles on the microgel assembly network structure framework, which are presented by the freeze-dried sodium alginate modified with phenylboronic acid. This shows that through capillary force, the phenylboronic acid modified polymer material can diffuse into the gaps of the microgel, and then through dynamic chemical bonding, the microgel balls can be connected. In addition, since the phenylboronic acid modified polymer material degrades quickly, larger pores can be formed after degradation, which is conducive to mass transfer.

[0191] (8) The cell survival status in the microgel assembly material prepared in Example 5 was characterized. The test results are as follows: Fig. 9 As shown:

[0192] Specifically: Confocal images of live-dead staining of pancreatic islet cells cultured in the microgel self-assembly material prepared in Example 5 for 1 day, wherein (a) is a microscope image at 40 times; (b)-(d) are fluorescence microscope images, Calcein AM (green, live cells), PI (red, dead cells): (b) live-dead co-staining; (c) live cell staining; (d) dead cell staining.

[0193] Depend on Fig. 9 It can be seen that the bionic environment of the microgel assembly material is suitable for the adhesion, proliferation and differentiation of biological cells.

[0194] (9) The microgel assembly material prepared in Example 6 is shown in the following photo. Fig.10 As shown, from Fig.10 It can be seen that carboxymethyl chitosan modified by phenylboronic acid can assemble hydroxyl-containing microgels into a whole.

[0195] (10) The microgel assembly material prepared in Comparative Example 1 is shown in the following figure. Fig.11 As shown, from Fig.11 It can be seen that the microgel spheres are dispersed in the solution and are not connected to each other. This shows that even if the unmodified CMC penetrates into the gaps of the microgels, it is difficult for the microgels to assemble into a whole due to the lack of dynamic chemical bonding.

[0196] (11) The microgel assembly material prepared in Comparative Example 2 is shown in the following photo. Fig.12 As shown, from Fig.12 It can be seen that the microgel spheres without PVA are also dispersed in the solution and are not connected to each other. This shows that even if CMC-BA penetrates into the gaps of the microgel, it is still difficult for the microgel to assemble into a whole because the microgel spheres lack groups that can react with phenylboronic acid.

[0197] (12) The microgel assembly material prepared in Comparative Example 3 is shown in the following photo. Fig.13 As shown, from Fig.13It can be seen that when PEGDA-CMC-BA microgel spheres are added to the PVA solution, there are large gaps between the spheres and they are not connected to each other. This is because the number of phenylboronic acid groups grafted onto CMC is limited, and when CMC-BA is added to the cross-linked microgel spheres, the movement of the CMC-BA molecular chain is restricted, making it difficult to bond with PVA through chain movement to form an assembled material.

[0198] It should be noted that, the “room temperature” in this article, unless otherwise specified, is approximately 25° C.; the meaning of “approximately” for numerical values ​​in this article is an error of ±2%.

[0199] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A microgel assembly material, characterized in that: The raw materials for preparing the assembly material include microgels and a phenylboronic acid-modified polymer solution, wherein the phenylboronic acid-modified polymer solution penetrates between the microgels through the action of capillary force and forms a dynamic chemical bond with the microgels; the phenylboronic acid-modified polymer is obtained by amidation reaction of aminophenylboronic acid and a carboxyl-containing polymer material; The preparation method of the microgel assembly material comprises the following steps: dripping the aqueous solution of the phenylboronic acid modified polymer material into the microgel to obtain the assembly material; the mass ratio of the microgel to the phenylboronic acid modified polymer material in the phenylboronic acid modified polymer solution is (25-1000): 1; the mass fraction of the phenylboronic acid modified polymer material in the phenylboronic acid modified polymer solution is 1-8%; The raw materials for preparing the microgel include polyvinyl alcohol and polyethylene glycol diacrylate; the mass ratio of the polyvinyl alcohol to the polyethylene glycol diacrylate is (0.8-1.2):1; the pore size of the microgel is 20-60nm; and the porosity of the microgel is 60%-80%.

2. The microgel assembly material according to claim 1, characterized in that: The mass ratio of the microgel to the phenylboronic acid modified polymer solution is (0.5-20):

1.

3. The microgel assembly material according to claim 1, characterized in that: The carboxyl-containing polymer material includes at least one of sodium carboxymethyl cellulose, chondroitin sulfate, hyaluronic acid, gelatin, carboxymethyl chitosan, collagen or sodium alginate.

4. The microgel assembly material according to claim 1, characterized in that: The mass ratio of the aminophenylboronic acid to the carboxyl-containing polymer material is (1-10):

1.

5. The microgel assembly material according to claim 1, characterized in that: The assembly material is a microgel assembly material containing alcoholic hydroxyl groups.

6. The microgel assembly material according to claim 1, characterized in that: The microgel contains alcoholic hydroxyl groups.

7. The microgel assembly material according to claim 1, characterized in that: The microgel is a semi-interpenetrating network microgel.

8. The microgel assembly material according to claim 1, characterized in that: The microgel is a microgel that wraps cell tissue.

9. The microgel assembly material according to claim 8, characterized in that: The cell tissue includes cells.

10. The microgel assembly material according to claim 8, characterized in that: The cells include a population of cells.

11. A method for preparing the microgel assembly material according to claim 1, characterized in that: The method comprises the following steps: allowing the phenylboronic acid modified polymer solution to penetrate between microgels through the action of capillary force and construct dynamic chemical bonds between the microgels to obtain the assembly material.

12. The microgel assembly material according to claim 11, characterized in that: The method also includes a step of preparing the microgel, which specifically includes: using polyvinyl alcohol and a water-soluble photosensitive polymerization monomer as polymerization monomers and adopting microfluidic technology to prepare the microgel.

13. A 3D cell culture carrier, characterized in that: The invention comprises at least one of the microgel assembly material according to any one of claims 1 to 10 or the microgel assembly material prepared by the method according to any one of claims 11 to 12.

14. A biomaterial, characterized in that: The invention comprises at least one of the microgel assembly material according to any one of claims 1 to 10 or the microgel assembly material prepared by the method according to any one of claims 11 to 12.

15. A medical product, characterized in that: The invention comprises at least one of the microgel assembly material according to any one of claims 1 to 10 or the microgel assembly material prepared by the method according to any one of claims 11 to 12.

16. The medical product according to claim 15, characterized in that The medical products include medical materials or medical devices.

17. Use of the microgel assembly material according to any one of claims 1 to 10 or the microgel assembly material prepared by the method according to any one of claims 11 to 12 in the preparation of biomaterials or medical products.